Comparative Analysis of Mechanical and Water Absorption Properties of Nano/micro-sized Alumina Filler Based Glass-Jute Hybrid Composites - Ramanuj Kumar; Singh, Kartik; Gogna, Ekta; Ranjan Sinha, Himansu; Kumar Sahoo, Ashok (International Journal of Integrated Engineering, 2020)
In recent years, the addition of nano and micro size filler material for fabricating composite materials are emerging concept through which mechanical properties of the composite can be enhanced. Filler based hybrid polymer composite materials are substituting metallic materials because of their low specific wear rate, high specific strength modulus, and less water absorption. In current work, nano and micro Al2O3 filler based Glass-Jute hybrid composite have been fabricated to study the mechanical properties like hardness, impact test, specific wear rate, and flexural strength for each type of composite sample. Water absorption analysis is also carried under three different fluid media namely normal water, river water and de-ionized water-based Al2O3 nanofluid. Nano filler enriched composite attributed the higher magnitudes of hardness, impact strength, flexural strength and lower value of specific wear rate and water absorption compared to micro and normal composites. However, a nanofiller based composite is more suitable for automotive, aerospace and ship manufacturing industries.